Programa de entrenamiento de la resistencia aeróbica en el crédito de balonpesado de la universidad del Quindío (2019)
The objective of this study was to determine the effects of a training program on the students aerobic capacity in the course: Balón-pesado at the University of Quindío. In order to carry out this research, three tests were established: one pre-test, an intermediate test and a post-test to evaluate the Vo2Max of each student through a field test (Leger Test). 16 people of several professional careers were involved in this research, with different physical ability that met the inclusion criteria. The program lasted 3 months, in which three sessions were conducted one hour per week. The investigation had a quantitative approach with an exploratory scope and pre-experimental design which counted on the participation of one group, the experimental one. The results obtained were analyzed by means of the software Jamovi 0.9.1.12, which enabled the description of variables to demonstrate what the effects of the program were. As a result, it was proven that in the third assessment the aerobic capacity reached the upper limit in comparison with other variables. In a similar way, the Vo2Max attained a better performance after the sixth week of intervention. As a conclusion, a program of medium intensity with a duration of 3 months got meaningful effects in the Vo2Max.